PERKEMBANGAN POLA PERILAKU MAHASISWA PENDIDIKAN SEJARAH DALAM PEMBELAJARAN MASA COVID-19 - Wisnu Wisnu; Sumarno Sumarno; Agus Trilaksana; RIyadi Riyadi (Universitas Negeri Surabaya, 2020)
Abstract This paper reveals the behavior of historical education students in dealing with the impact of the Covid-19 outbreak. Responding to this situation, the State University of Surabaya followed the directives of the Directorate of Higher Education to change conventional learning to online lectures. The policies issued by State University of Surabaya affect aspects of student activities, and relate to individual student activities in dealing with learning systems that are enforced online or non-conventional. The purpose of this study seeks to reveal how the behavior of History Education students in adapting and at the same time understanding the process of forming new behavior patterns from students during online learning after facing the Covid-19 situation. Student behavior patterns towards aspects of online learning and aspects of family life affect the emergence of new forms of behavior both in the form of attitudes and cultures that come into contact with IT devices. This research uses a qualitative approach with descriptive methods. In the early stages of collecting data from various sources, especially students through online media in the form of narrative text, expressions, words, opinions, and ideas. Furthermore, by using the descriptive-qualitative method, it is attempted to describe events, circumstances, objects, and things related to variables that can be explained by the problem under study. This study describes the phenomenon of student behavior patterns in using online media. The results of this study can open and broaden people's insights about understanding the lecture situation that is no longer carried out conventionally but with new patterns by utilizing technology or online media. This research can also foster situational awareness among the community, that the process of adaptability of history education students has taken place in maintaining the continuity of the learning process. An understanding of the results of research can also be used as material for consideration in issuing policies in Unesa and the government in general. In addition, this research will also produce articles that will be sent to accredited scientific journals. Key Word: Behavior, student, learning history education